Balancing Systems Engineering Rigor with Agile Software Development Flexibility. Issue 2 (5th July 2018) - Tolentino, Glenn; Wood, John
ABSTRACT: Conflict among team members predictably emerged in a successful US Department of Defense project when leadership inserted agile software development methodologies into the well‐established systems engineering‐oriented work environment. Yet, despite the conflict, project leadership saw inherent value in both agile development and systems engineering methodologies. So, instead of choosing one methodology over the other, project leadership took action to structure an approach that mitigated the conflict and enabled the project stakeholders to enjoy the benefits each methodology provided. This paper describes the project team's problem space analysis, the analysis results, and the balanced approach they developed with the goal of advancing the project to the next level.